Effect of hyoscine N‐butylbromide on adenoma detection rate: Meta‐analysis of randomized clinical trials. Issue 3 (16th October 2014) - Madhoun, Mohammad F.; Ali, Tauseef; Tierney, William M.; Maple, John T.
Abstract : Background and Aim: Anti‐spasmodic drugs may facilitate mucosal inspection during colonoscopy. The impact of hyoscine N ‐butylbromide (HBB) on polyp detection rate (PDR) and adenoma detection rate (ADR) is unclear. Methods: We conducted a reproducible literature search of multiple databases. Two reviewers independently compared manuscripts for PDR, ADR, advanced adenoma detection rate (AADR), and rates of complications. Pooling was conducted by fixed‐effects and random‐effects models. Relative risk (RR) estimates were calculated (95% confidence interval). I 2 index assessed heterogeneity. Results: Patient demographics were comparable. The pooled analysis showed a trend toward improving PDR and ADR among the HBB group compared with the placebo group but failed to reach statistical significance, (46% vs 43%, RR = 1.08 [0.94, 1.25], P = 0.27), (31% vs 28%, RR = 1.12 [0.97, 1.29], P = 0.11) respectively. Conclusion: HBB during colonoscopy may provide marginal improvements in ADR and PDR. However, heterogeneity in the available data precludes firm conclusions at this time.